THE MEDIATING ROLE OF AFFECTIVE COMMITMENT AND POLICY IMPLEMENTATION IN IMPROVING THE PERFORMANCE OF BUMDES - Suhardiman, Suhardiman; Juniarti, Atty; Indra Setia, Bayu (Faculty of Economic and Business, University of Pasundan, 2024)
This research aims to examine how leadership influences the performance of BUMDes Directors, mediated by Affective Commitment and Policy Implementation. BUMDes is a strategic business entity for the economic development and welfare of village communities.The study surveyed 253 advanced-category BUMDes directors in Riau Province, using SEM-PLS analysis. The findings indicate that leadership has a significant positive influence on Affective Commitment and Policy Implementation by the directors. Effective leadership shapes directors' affective commitment and encourages active participation in policy implementation and goal achievement. Leadership also directly influences BUMDes director performance, mediated by Affective Commitment and Policy Implementation. These findings highlight the vital role of leadership in enhancing BUMDes director performance through affective commitment and policy implementation. The research implications can guide decision-making and policy improvement related to BUMDes, as well as contribute to literature on the role of BUMDes in sustainable village development.